Weight loss induces changes in adaptive thermogenesis in female and male physique athletes - Isola, V.; Hulmi, J. J.; Petäjä, P.; Helms, E. R.; Karppinen, J. E.; Ahtiainen, J. P. (Applied Physiology, Nutrition, and Metabolism, 2023)
Physique athletes lose substantial weight preparing for competitions, potentially altering systemic metabolism. We investigated sex differences in body composition, resting energy expenditure (REE), and appetite-regulating and thyroid hormone changes during a competition preparation among drug-free physique athletes. The participants were female (10 competing (COMP) and 10 nondieting controls (CTRL)) and male (13 COMP and 10 CTRL) physique athletes. COMP were tested before they started their diet 23 weeks before competing (PRE), during their diet one week before competing (MID), and 23 weeks after competing (POST), whereas CTRL were tested at similar intervals but did not diet. Measurements included body composition by dual-energy X-ray absorptiometry, muscle size, and subcutaneous fat thickness (SFA) by ultrasound, REE by indirect calorimetry, circulating ghrelin, leptin T3, and T4 hormone analysis. Fat mass (FM) and SFA decreased in both sexes (p < 0.001), while males (p < 0.001) lost more lean mass (LM) than females (p < 0.05). Weight loss, decreased energy intake, and increased aerobic exercise (p < 0.05) led to decreased LM- and FM-adjusted REE (p < 0.05), reflecting metabolic adaptation. Absolute leptin levels decreased in both sexes (p < 0.001) but more among females (p < 0.001) due to higher baseline leptin levels. These changes occurred with similar decreases in T3 (p < 0.001) and resting heart rate (p < 0.01) in both sexes. CTRL, who were former or upcoming physique athletes, showed no systematic changes in any measured variables. In conclusion, while dieting, female and male physique athletes experience REE and hormonal changes leading to adaptive thermogenesis. However, responses seemed temporary as they returned toward baseline after the recovery phase.